Choriocarcinoma with Pulmonary and Spinal Metastases : A Case Report - Syafar, Fardani Putra; Muhammad, Syammel; Antonius, Puja Agung (Andalas Obstetrics And Gynecology Journal, 2023)
Background : Choriocarcinoma is extremely malignant tumor contains of anaplastic trophoblast and prominent hemorrhage, necrosis, and vascular invasion.Â Choriocarcinoma is a rare, aggressive neoplastic type of trophoblastic disease. This condition grow rapidly and can metastasize to the lung and liver. There are few cases of choriocarcinoma metastases to the spine that have been reported. Case Report : A 28-year-old woman with complaints of haemoptoe and shortness of breath. Previously the patient complained of not feeling the sensation for defecation and micturition. The patient had been diagnosed with choriocarcinoma since 3 years ago, refused to have a hysterectomy and had received chemotherapy 12 times in the first year with choriocarcinoma, but dropped out of chemotherapy in the second year, then came with a worsening condition a year later. The results of the chest x-ray and lumbar MRI showed suspicion of metastases to the lungs and spine. The patient was continued with chemotherapy with paclitaxel and carboplatin and was monitored with periodic beta HCG evaluation.Â Choriocarcinoma a have different prognoses depending on stage and onset. In these patients, based on FIGO staging, she has reached stage IV and also suspected chemotherapy-resistantÂ Gestational Trophoblastic Neoplasia (GTN), worsened by disobedience to previous treatment. ManyÂ patients with GTN require multiple regimens with or without surgery to achieve complete remission.